2016
DOI: 10.15835/nbha44110144
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters and Antioxidant Activity of Three Clover Species in Relation to the Livestock Diet

Abstract: Products of metabolism that are directly involved in growth, development and reproduction and also secondary products of metabolism were studied in 16 natural populations of three species of the genus Trifolium (T. repens -four populations, T. alpestre -three populations, T. pannonicum -nine populations), collected from the central Balkans region, i.e. territory of Serbia. Statistical analysis showed the presence of variability in all species of the test material. The best quality of dry matter, estimated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…lignans (Dai and Mumper, 2010). Various epidemiological studies have confirmed the anti-inflammatory, estrogenic, antimicrobial, antiallergenic and antitumor properties of the phenolic compounds in the Trifolium genus (Khorasani Esmaeili et al, 2015;Petrović et al, 2016). Isoflavones, the major phenolics present in the red clover, are categorized as phytoestrogens.…”
Section: Introductionmentioning
confidence: 99%
“…lignans (Dai and Mumper, 2010). Various epidemiological studies have confirmed the anti-inflammatory, estrogenic, antimicrobial, antiallergenic and antitumor properties of the phenolic compounds in the Trifolium genus (Khorasani Esmaeili et al, 2015;Petrović et al, 2016). Isoflavones, the major phenolics present in the red clover, are categorized as phytoestrogens.…”
Section: Introductionmentioning
confidence: 99%
“…Biochanin A also shows a plenitude of biological activities such as hypoglycemic, anti-microbial, anti-cancer, anti-oxidant, as well as osteogenic and anti-inflammatory properties [ 14 , 15 ]. Other polyphenolic compounds, such as flavonoids, polyphenolic amides and phenolic acids, which are present in red clover, can also contribute to its antioxidant potential [ 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous articles confirming antioxidant activity of Trifolium pratense L. The results of research suggested the great value of flowers and leaves of Trifolium species for their use in phytotherapy, due to their content of polyphenols responsible for the antioxidant activities; phenols in plants can also act as deterrents against herbivores, as antiviral and antimicrobial factors and photoprotectants against UV irradiation [ 19 , 20 , 21 ]. Using the right extraction method more phenolic compounds can be extracted, therefore, the antioxidant activity can be increased.…”
Section: Introductionmentioning
confidence: 99%